2020
DOI: 10.21037/tcr.2019.07.07
|View full text |Cite
|
Sign up to set email alerts
|

Examining the evolving utility of 18FDG-PET/CT in breast cancer recurrence

Abstract: Many studies have demonstrated the utility of 18 fluorodeoxyglucose-positron emission tomography/computed tomography ( 18 FDG-PET/CT) scan in evaluating breast cancer recurrence in subsets of patients based on age, histological subtype and cancer stage to guide response to conventional chemoradiation guidelines during treatment of metastatic breast cancer disease. This literature review focuses on the breakthrough of 18 FDG-PET/CT imaging wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The majority of early BC patients undergo local excision surgery and postoperative radiotherapy, with a 5-year relative survival rate of approximately 98% for those diagnosed with localized disease. While locoregional recurrence carries a poor prognosis, early detection and staging of recurrence can improve survival [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of early BC patients undergo local excision surgery and postoperative radiotherapy, with a 5-year relative survival rate of approximately 98% for those diagnosed with localized disease. While locoregional recurrence carries a poor prognosis, early detection and staging of recurrence can improve survival [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography (PET) images of the radiotracer 2-deoxy-2-[ 18 F]-fluoro-D-glucose (FDG) are used widely for tumour staging and assessment of treatment response [ 1 ]. In routine practice single static FDG-PET images are collected around an hour after tracer injection.…”
Section: Introductionmentioning
confidence: 99%
“…Djassemi N. et al reported that elevated serum tumor markers can be useful prognostic markers of recurrence in asymptomatic breast cancer patients[4]. In another review, high levels of CA 15.3 marker indicate, almost certainly, the presence of metastatic disease[5].…”
mentioning
confidence: 99%